Les conceptions initiales des élèves turcs de CM2 relatives aux séismes - Burckin Dal (Unité Mixte de Recherche 8504 Géographie-cités, 2005)
Knowledge about earthquakes is therefore a complex knowledge, derived from a long history, transformed into knowledge to be taught through the choice of official programs, textbooks, taking into account the process of building knowledge in children, and those of the elaboration of concepts in the field of the sciences of the terrestrial space, enlightened by J. Piaget and other researchers. The recognition of representations can constitute a basis for organizing strategies adapted to the students. This article describes what specific Turkish children's conceptions of earthquakes were before they received any courses on these subjects. We conducted a series of surveys on this topic and analyzed the results.